2004
DOI: 10.1074/mcp.m400081-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

The Phox Homology (PX) Domain Protein Interaction Network in Yeast

Abstract: Phosphoinositides (PIs)1 act as signaling molecules in a variety of cellular processes including vesicular trafficking and cell motility (1-3). PI signaling is mediated by proteins that contain one or several lipid-binding domains such as PH, FYVE, ENTH, ANTH, FERM, PHD, Tubby, and C2 domains, all of which have been reported to bind PIs. Recently, the PX domain was shown to represent another PI-binding domain (reviewed in Refs. 4 -7).Phox homology (PX) domains were originally identified as a common motif of ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 51 publications
3
39
0
Order By: Relevance
“…However, physical interactions have been observed between Mvp1 and three nuclear proteins, Std1, Yra2, and Srb7 (Schmidt et al 1999;Hazbun et al 2003;Vollert and Uetz 2004;Titz et al 2006). Similarly, Spo14 physically interacts with Dcp2 (Fromont-Racine et al 1997) and genetically with the transcription factor Ste12 (Hairfield et al 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, physical interactions have been observed between Mvp1 and three nuclear proteins, Std1, Yra2, and Srb7 (Schmidt et al 1999;Hazbun et al 2003;Vollert and Uetz 2004;Titz et al 2006). Similarly, Spo14 physically interacts with Dcp2 (Fromont-Racine et al 1997) and genetically with the transcription factor Ste12 (Hairfield et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Mvp1, a protein required for sorting proteins to the vacuole (Ekena and Stevens 1995), physically interacts with three Nonet and Young (1989) nuclear proteins, Std1, Yra2, and Srb7 (Schmidt et al 1999;Hazbun et al 2003;Vollert and Uetz 2004;Titz et al 2006). Similarly, Spo14, a phospholipase D involved in Sec14p-independent secretion and required for meiosis and spore formation (Rudge et al 2002;Nakanishi et al 2006), physically interacts with Dcp2, (Fromont-Racine et al 1997) and genetically interacts with the transcription factor Ste12 (Hairfield et al 2001).…”
Section: Identification Of Conserved Domains Of the Rna Polymerase IImentioning
confidence: 99%
“…Although the first PX domains were found to bind PtdIns3P (752,1750), and all yeast PX domains bind this lipid (1782), some metazoan PX domains bind PtdIns(4,5)P 2 (327, 810), and the lipid-binding specificity of many mammalian PX domains remains unknown. It is also important to note that PX domains also bind proteins (1540,1643). Recent studies also suggest that class II PI3Ks produce some of the PtdIns3P in higher eukaryotes (370,970,1700), and the molecular cloning of the type II PI4Ks (108, 1058) revealing their presence in endosomes (83, 1060) also suggested the involvement of these latter enzymes in endocytic trafficking in mammalian cells (83, 1060).…”
Section: Ptdins3p and Ptdins(35)p 2 In Endomembranesmentioning
confidence: 99%
“…Indeed, the insulin-induced membrane translocation of the p47 phox PX domain has been reported to be only partially dependent on PtdIns(3)P binding (Zhan et al, 2002). In a recent study several PX domains of yeast were found to have protein binding partners in a genome-wide two-hybrid screen (Vollert and Uetz, 2004). Many of the interacting proteins are membrane proteins involved in vesicular trafficking and it will be important to determine whether a common PX-domaininteracting motif can be identified in these proteins.…”
Section: Ph- Ptb-and Ferm Domainsmentioning
confidence: 99%